Implementation of A Web-Based Bogor Peak Tourism Information System - Yudistira Soegoto; Ari Fauzi; Muhammad Fariel Raihan Haque; Shinta Ayu Purnamasari (International Journal of Research and Applied Technology (INJURATECH), 2022)
Puncak Bogor is a mountainous tourist attraction in the Bogor area and Cianjur regency which is visited by many tourists and makes the peak of Bogor as one of the right choices to relieve fatigue from daily activities. Because it is too crowded and crowded with visitors who come, therefore many entrepreneurs to open tourist attractions, and cause congestion in the direction of Puncak. The purpose of designing this web-based Puncak Bogor Tourism information system is to make it easier for tourists to vacation in Puncak Bogor, this design uses the method of data collection and analysis process obtained from the tourism office, transportation agency, and BMKG. As a result of designing this system, 90% of web users find it easiest to travel to the top of Bogor. Because the vacillation of tourists to go on vacation is resolved by the existence of the web. It can be concluded, the existence of this web can help people who experience fatigue from the work that has been carried out and want to take a vacation with their families. To find out the route to be passed is safe and smooth, then of course you will look for information about travel routes that can facilitate the journey to the destination.